Synthesis of nanocrystalline PbS for promising solar cells using microwave-assisted chemical bath deposition - Hisham, M.; Hassan, Z. (2018)
Lead sulfide (PbS) Nano cubes have been successfully deposited onto glass substrate via microwave assisted chemical bath deposition technique. Morphological structural and optical analysis revealed that high quality nanocrystalline PbS were obtained using microwave-assisted chemical both deposition technique . Optical studies indicated that the energy band gap has significantly increased for the prepared. PbS thin fibre due to the confinement effect. A promising material for solar cell application using low cost fabrication method in a relatively short deposition time was introduced.